Archaeological paleography : a proposal for tracing the role of interaction in Mayan script innovation via material remains - Englehardt, Joshua, (Archaeopress pre-Columbian archaeology ;, 2015)
This volume explores the development of the Maya writing system in Middle-Late Formative and Early Classic period (700 BC-AD 450) Mesoamerica.